Pengaruh Kepemimpinan Transformasional Kepala Sekolah dan Budaya Organisasi Terhadap Kinerja Guru di SMK Negeri 1 Bone Raya Kabupaten Bone Bolango - Hafied, Kaharuddin Abdul (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik, 2025)
This research was made with the purpose; 1) An analyze the influence of transformational leadership head master toward teacher performance at SMK Negeri 1 Bone Raya; 2) An analyze the influence of organization culture toward teacher performance; 3) An analyze the influence of transformational leadership the head master and organization culture by do together toward teacher performance at SMK Negeri 1 Bone Raya.  This research used data primer through the observation 35 teacher’s and the educator’s with the technique of collecting sample by using probability sampling as surfeited sampling or census. This survey has done on November until December 2016. The analysis data using linier regression analysis helped by SPSS 16.0. The result of this research show that: 1) Transformational leadership of head master there is positive influential but not significant toward teacher’s performance with value t1count < ttable(0,05)(33)  = 1,102  < 1,697 and value r = 0,337, 2) Organization culture also there is positive influential and significant toward teacher’s performance with value t2count > ttable(0,05)(33)  = 6,151 > 1,697 and value r = 0,769 and 3) Transformational leadership of head master and organization culture all of them have positive influential and significant toward teacher’s performance with value Fcount > Ftable(0,95)(2,32)  = 24,716 > 3,30 and value r = 0,779. The implication managerial in this research is every organizer of education should commit also an improving application transformational leadership of head master and organization culture to improving teacher’s performance at SMK Negeri 1 Bone Raya regency Bone Bolango.